Crystal structure of a compact three-dimensional metal-organic framework based on Cs+ and (4,5-dicyano-1,2-phenylene)bis(phosphonic acid) - Mendes, Ricardo F. (2017)
A new metal organic framework compound, poly[[ 7-dihydrogen (4,5-dicyano- 1,2-phenylene)diphosphonato](oxonium)caesium], [Cs(C8H4N2O6P2)(H3O)]n (I), based on Cs+ and the organic linker 4,5-dicyano-1,2-phenylene)bis(phosphonic acid, (H4cpp), containing two distinct coordinating functional groups, has been prepared by a simple diffusion method and its crystal structure is reported. The coordination polymeric structure is based on a CsO8N2 complex unit comprising a monodentate hydronium cation, seven O-atom donors from two phosphonium groups of the (H2cpp)2 ligand, and two N-atom donors from bridging cyano groups. The high level of connectivity from both the metal cation and the organic linker allow the formation of a compact and dense threedimensional network without any crystallization solvent. Topologically (I) is a seven-connected uninodal network with an overall Scha¨ fli symbol of {417.64}. Metal cations form an undulating inorganic layer, which is linked by strong and highly directional O H O hydrogen-bonding interactions. These metallic layers are, in turn, connected by the organic ligands along the [010] direction to form the overall three-dimensional framework structure.